The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1128/aem.00637-07
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and Response of Bifidobacterium animalis subsp. lactis to Bile: a Proteomic and Physiological Approach

Abstract: Bile salts are natural detergents that facilitate the digestion and absorption of the hydrophobic components of the diet. However, their amphiphilic nature makes them very inhibitory for bacteria and strongly influences bacterial survival in the gastrointestinal tract. Adaptation to and tolerance of bile stress is therefore crucial for the persistence of bacteria in the human colonic niche. Bifidobacterium animalis subsp. lactis, a probiotic bacterium with documented health benefits, is applied largely in ferm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
114
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 60 publications
11
114
0
Order By: Relevance
“…Schell et al (26) suggested that these enzymes might be one of the primary defense mechanisms against oxidative stress in bifidobacteria, and other research has shown upregulation of thioredoxin, thioredoxin reductase, and peroxiredoxin genes in response to oxygen stress (27,28). Interestingly, exposure to bile can also produce an oxidative stress response via generation of oxygen free radicals (29), and Sanchez et al (30) found that bile stress induced a thioredoxindependent thiol peroxidase in B. animalis subsp. lactis.…”
Section: Resultsmentioning
confidence: 99%
“…Schell et al (26) suggested that these enzymes might be one of the primary defense mechanisms against oxidative stress in bifidobacteria, and other research has shown upregulation of thioredoxin, thioredoxin reductase, and peroxiredoxin genes in response to oxygen stress (27,28). Interestingly, exposure to bile can also produce an oxidative stress response via generation of oxygen free radicals (29), and Sanchez et al (30) found that bile stress induced a thioredoxindependent thiol peroxidase in B. animalis subsp. lactis.…”
Section: Resultsmentioning
confidence: 99%
“…The bifid shunt has been partially characterized in terms of enzymatic activities (9,19), and the labeling pattern of end products derived from Glc metabolism in Bifidobacterium bifidum ATCC 29521 was investigated by 13 C nuclear magnetic resonance (NMR) using as metabolic tracers Glc specifically labeled on carbons 1 and 3 (20). In vivo 13 C NMR is a noninvasive technique that allows the monitoring, online and in real time, of the concentrations of end products and intracellular metabolites, as well as the rates of substrate consumption, during the metabolism of labeled substrate by nongrowing cells under controlled temperature and atmosphere conditions (21). This technique has facilitated the study of different pathways in various species, such as Lactococcus lactis, Staphylococcus aureus, and Escherichia coli (22)(23)(24).…”
mentioning
confidence: 99%
“…The fructose 6-phosphate phosphoketolase (Xfp) is the characteristic enzyme of this path, which holds a dual substrate specificity, acting on fructose 6-phosphate or xylulose 5-phosphate to produce aldose phosphate, acetyl phosphate, and H 2 O (10-12). Glyceraldehyde 3-phosphate and acetyl phosphate are further metabolized to produce the end metabolites of the pathway, with acetate, lactate, and ethanol being the most abundant (13).…”
mentioning
confidence: 99%
“…In order to obtain bacterial strains with better resistance to stress, the selection of natural variants was previously applied to bifidobacteria, e.g., for resistance to cholate (20), acid (9,29), or bile (30). With the current work, we applied a similar approach that may be seen as an accelerated evolution of a bacterial strain: sequential selection of naturally occurring mutants showing an adaptation to specific physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, even in such a species, variations in stress tolerance have been documented (19). Robust stress-resistant mutants arise, sometimes spontaneously (9,20,29,30). Specific stress-tolerant mutants might thus be obtained by natural selection.…”
mentioning
confidence: 99%